Legal Measures to Protect Children’s Personal Data in the Digital Age: A Comparative Study of Laws in Thailand and Other Countries - Khirimasthong, Jidapha; Sarnnoi, Egkapong (Rajapark Journal, 2026)
This research aims to 1) study the issues concerning the protection of children’s personal data on online media, 2) examine Thailand’s legal measures related to the protection of children’s personal data on social media and compare them with legal measures in other countries, and 3) find appropriate legal solutions to the problems concerning the protection of children’s personal data in Thailand related to the protection of children’s personal data on online media. This is qualitative research using data collected from books, articles, theses, research reports, and related documents. The research findings indicate that the protection of children’s personal data on online media in Thailand lacks clear and comprehensive provisions, particularly regarding definitions, scope, parental consent, data controllers’ duties, and specific measures for social media. There are also problems with enforcement and coordination between agencies compared to foreign laws, such as GDPR and COPPA, which have more specific and effective measures. Solutions should include amending the Personal Data Protection Act B.E. 2562 (2019) to add specific provisions on children’s data, such as age-verification systems, restrictions on the use of data for marketing purposes, and increased penalties. Additionally, the Child Protection Act B.E. 2546 (2003) should be amended to address the digital context, promote knowledge in educational institutions, and develop effective remediation mechanisms to elevate the protection of Thai children to international standards.